A novel hybrid meshless method for seepage flows in non-homogeneous and anisotropic soils. Issue 2 (16th April 2018) - Hajiazizi, Mohammad; Graili, Adel
Abstract : Purpose: The purpose of this paper is to extend the scaled boundary radial point interpolation method (SBRPIM), as a novel semi-analytical scheme, to the analysis of the steady state confined seepage flows. Design/methodology/approach: This method combines the advantages of the scaled boundary finite element method and the BRPIM. In this method, only boundary nodes are used, no fundamental solution of the problem is required, and as the shape functions constructed based on the RPIM satisfy the Kronecker delta function property, the boundary conditions of problems can be imposed accurately and easily. Findings: Three numerical examples, including seepage flow through homogeneous and non-homogeneous soils, are analyzed in this paper. Comparing the flow net obtained by SBRPIM and other numerical methods confirms the ability of the proposed method in analyzing seepage flows. In addition, in these examples, the accuracy of the SBRPIM in modeling the velocity singularity at a sharp corner is illustrated. SBRPIM accurately models the singularity point in non-homogeneous and anisotropic soil. Originality/value: SBRPIM method is a simple effective tool for analyzing various kinds of engineering problems. It is easy to implement for modeling the velocity singularity at a sharp corner. The proposed method accurately models the singularity point in non-homogeneous and anisotropic soil.